Financial Incentives for Promoting Colorectal Cancer Screening: A Randomized, Comparative Effectiveness Trial. (November 2016) - Gupta, Samir; Miller, Stacie; Koch, Mark; Berry, Emily; Anderson, Paula; Pruitt, Sandi L; Borton, Eric; Hughes, Amy E; Carter, Elizabeth; Hernandez, Sylvia; Pozos, Helen; Halm, Ethan A; et al.
Abstract : OBJECTIVES: Offering financial incentives to promote or "nudge" participation in cancer screening programs, particularly among vulnerable populations who traditionally have lower rates of screening, has been suggested as a strategy to enhance screening uptake. However, effectiveness of such practices has not been established. Our aim was to determine whether offering small financial incentives would increase colorectal cancer (CRC) screening completion in a low‐income, uninsured population. METHODS: We conducted a randomized, comparative effectiveness trial among primary care patients, aged 50–64 years, not up‐to‐date with CRC screening served by a large, safety net health system in Fort Worth, Texas. Patients were randomly assigned to mailed fecal immunochemical test (FIT) outreach ( n =6, 565), outreach plus a 5 incentive ( n =1, 000), or outreach plus a 10 incentive ( n =1, 000). Outreach included reminder phone calls and navigation to promote diagnostic colonoscopy completion for patients with abnormal FIT. Primary outcome was FIT completion within 1 year, assessed using an intent‐to‐screen analysis. RESULTS: FIT completion was 36.9% with vs. 36.2% without any financial incentive ( P =0.60) and was also not statistically different for the 10 incentive (34.6%, P =0.32 vs. no incentive) or 5 incentive (39.2%, P =0.07 vs. no incentive) groups. Results did not differ substantially when stratified by age, sex, race/ethnicity, or neighborhood poverty rate. Median time to FIT return also did not differ across groups. CONCLUSIONS: Financial incentives, in the amount of 5 or 10 offered in exchange for responding to mailed invitation to complete FIT, do not impact CRC screening completion.